Intermediate Goods Trade, Technology Choice and Productivity - Shin-Kun Peng; Raymond Riezman; Ping Wang (Center for Economic Studies and ifo Institute (CESifo), 2015)
We develop a dynamic model of intermediate goods trade in which the pattern and the extent of intermediate goods trade are endogenous. We consider a small open economy whose final good production employs an endogenous array of intermediate goods, from low technology (high cost) to high technology (low cost). The underlying intermediate goods technology evolves over time. We allow for endogenous markups and consider the effect of trade policy on both the intensive and extensive margins. We show that either domestic or foreign trade liberalization reduces the range of exports and the range of domestic intermediate goods production. Either type of trade liberalization reduces intermediate producer markups and increases final good output and average productivity, with stronger positive productivity effects for newly imported intermediate inputs. However, domestic trade liberalization results in lower aggregate and average technology for domestic intermediate good producers.
Keywords: D92; F12; O24; O33; 330; intermediate goods trade; technology choice; extensive versus intensive margin effect of trade liberalization